The Results of National Oral Health Survey, Mongolia - Jargaltsogt, Delgertsetseg; Bazar, Oyuntsetseg; Sharkhuu, Munkh-Od; Altansukh, Suvdanchimeg; Bazar, Amarsaikhan (Central Asian Journal of Medical Sciences, 2018)
Objectives: The aim of this study was to determine the status of oral health in Mongolia. Methods: The studied population was 1754 subjects who were selected from 4 age groups and from 11 regions of Mongolia. We collected data about dentition, gingival health, dental calculus, intervention urgency and denture usage. Results: The prevalence of dental caries and mean Decayed, Missed, Filled permanent teeth (DMFt)/ decayed, missed, filled primary teeth (dmft) were 82.9% and 5.9±4.6 among 5 year olds, 80.9% and 2.5±2.2 among 12 year olds, 97.8% and 9.5±5.2 among 35-44 year olds, 99.1% and 19.9±8.1 among 65-74 year olds (p<0.001). The prevalence of gingivitis was 4.6% , 21.2% , 36.3% , 11.5% and of calculus 0.5% , 7.1% , 53.1%, 24.2% , respectively above groups. The status of intervention urgency was 16.4%, 21.4% , 43.6% , 37.3% in the prompt treatment and 5.9%, 4.2% , 7.0% , 0.7% in immediate treatment recommended. The percent of people with removable denture among 65-74 year olds was higher than among 35-44 year olds. Conclusion: The prevalence of dental caries and their complications were in the high in Mongolia, and most of elderly people did not have their own natural teeth. These data indicate that effort to improve oral hygiene and prevent tooth decay are greatly needed throughout Mongolia.